NEXTHEIRS: BLOCKCHAIN BASED INHERITANCE MANAGEMENT SYSTEM USING QUANTUM RESISTANT - Sonali Ridhorkar; Vratik Zade; Vaibhav Mathane; Anmol Prince; Akshay Dhobale; Mayuri Kamdi, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
The rise of quantum computing necessitates strong cryptographic systems in blockchain applications to guard against vulnerabilities. This probe thoroughly examines the vulnerabilities inherent in conventional cryptographic protocols when pitted against the immense computational capabilities of quantum computers. It recommends the adoption of quantum-resistant alternatives to safeguard confidentiality and security in blockchain networks. The suggested "NextHeirs" offers a glimpse into decentralized inheritance systems through extensive review and integration of previous studies presented in this paper, which shows groundbreaking potential. NextHeirs represents a new way of transferring assets employing blockchain technology and quantum resistant algorithms which removes centralization security concerns and quantum computing vulnerabilities. NextHeirs ensures a sound, fair and secure framework for asset allocation by integrating provable Merkle trees that relate to the Base blockchain and secured by Quantum-Resistant Dilithium signatures. The paper also analyzes questions concerning non-parallelism of transactions as well as undetermined transaction details within blockchain networks, thus indicating an urgent need for strong data protection strategies and precise testing processes particularly in respect of smart contracts. In terms of developing future blockchain systems, it primarily seeks to enhance post-quantum signature schemes to improve resilience of key components such as InterPlanetary File System (IPFS) while at the same time boosting efficiency. The understanding and guidance required for the development of protected, distributed systems that are not easily affected by the changing threats brought about by quantum computing to guarantee blockchain applications’ durability and integrity into more digitalized globe.